Fatores potencializadores dos atropelamentos de fauna silvestre no trecho da GO-080 entre Goiânia e Petrolina de Goiás - Cortez, Helena Bernardes (2021)
Every year, about 473,000,000 vertebrate animals are run over on Brazilian highways, which are of great importance in the mobility of people and products across the country. Its constructions frag ment and isolate vegetated areas, harming biodiversity. The barrier effect imposed by highways can isolate the fauna and flora in their habitats, making it difficult to diversify DNA between species, which can lead to the extinction of countless individuals. This work had the objective of evaluating the conditions of the landscape of the GO-080 highway, between the section that connects Goiânia to Petrolina de Goiás, as potentiators of road kills of wild fauna. 31 field surveys were carried out, with 76 records of the occurrence of vertebrate animals being run over in two different periods, from June 2019 to March 2020 and November 2020 to March 2021 due to the sudden drop in the occur rence of wild fauna being run over in the period rainy. Data collection enabled the generation of cartographic products and statistical analysis of Ripley-2D K and Kernel density. Statistical analysis was applied using Siriema 2.0 and QGIS version 3.16 software. The definition of fauna running over hotspots was made through the union of static data and heat maps, which made it possible to divide the study area into 10 tracks in order to analyze the potential for fauna running over. By collecting secondary data from the MapBiomas Land Use and Coverage Program for the year 2019, it was possible to analyze the classes considering the amount of fragment and their respective percentages that defined the areas of the hotspots. During the inspections, three birds, one reptile and 59 mammals were found, 13 animals were not identified, highlighting the finding of 17 giant anteaters and 10 otters. As animals at risk of extinction, the anteaters stand out, another species found that caused strangeness were the otters, as they are animals of aquatic habitats and difficult to cross. In the re sults, it was observed that 38% of roadkills occurred in winter, showing that the highest occurrence was in the dry period. Areas of plant formation cover 77.05% of the surroundings of the road where 41 animal carcasses were found in an area of forest formation, totaling 53.9% of the observed rec ords. Only two carcasses were found in the urban perimeter. A driver of the fauna trampling found was the North South Railway, due to the proximity of the domain tracks of the two modals. This is configured in a greater difficulty in the crossing of the animals, allowing a greater number of tram pling. In order to guarantee the preservation of species, it is necessary to implement fauna passages that allow animal life and genetic variability between the fragments of the vegetated areas, especially in the hotspots found. Educating actions for drivers must be implemented, along with signs and ele ments that reduce speed on the road. In order to verify the relationships between wild animals and the GO-080, it is essential to monitor wild animals being run over during all months of the year, instead of quarterly inspections as recommended by environmental agencies.